2021
DOI: 10.3389/fpsyt.2021.626121
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Anti-flotillin 1/2 Autoantibody-Associated Atypical Dementia

Abstract: Flotillin proteins are involved in neurodegeneration and T-cell immunity. Here, we report the case of 65-year-old woman who presented with dementia, depressive symptoms, and a patient history involving speech problems. As diagnostics methods we applied magnetic resonance imaging, clinical examination, extensive neuropsychological testing, and cerebrospinal fluid analysis. Neuropsychological testing revealed major cognitive decline in attentional, executive, and memory functions together with impaired activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…We thus conducted a pilot trial relying on retrospective data to identify whether progressing cognitive dysfunction is more prominent in NABD than in AD. Our second point of inquiry concerned the axonal neurodegeneration detected in some patients with neural antibody-associated dementia (2,(8)(9)(10)(11) to see if tau pathology is associated with rapidly worsening cognitive impairment in both dementia types. We wondered 1) whether the degree of axonal neurodegeneration differs in NABD from that in AD and 2) if the axonal degeneration correlates with the longitudinal time course of cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…We thus conducted a pilot trial relying on retrospective data to identify whether progressing cognitive dysfunction is more prominent in NABD than in AD. Our second point of inquiry concerned the axonal neurodegeneration detected in some patients with neural antibody-associated dementia (2,(8)(9)(10)(11) to see if tau pathology is associated with rapidly worsening cognitive impairment in both dementia types. We wondered 1) whether the degree of axonal neurodegeneration differs in NABD from that in AD and 2) if the axonal degeneration correlates with the longitudinal time course of cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this this version posted September 14, 2022. ; https://doi.org/10.1101/2022.09.14.22278529 doi: medRxiv preprint findings were compatible with the diagnosis of limbic encephalitis and patient responded to corticosteroids, which supported the autoimmune etiology. In neurodegenerative disorders, a case of atypical dementia associated with anti-FLOT-1/2 antibodies is also published (19), without other similar cases reported. The relevance and pathogenicity of these antibodies in this group of diseases is difficult to elucidate as only isolated cases are reported and further reports would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, a search of the literature revealed that anti-flotillin autoantibodies were mostly identified in reports of multiple sclerosis patients except for one recent case which reported anti-flotillin 1/2 autoantibody-associated atypical dementia ( 8 ). Furthermore, the patient’s optic nerve and spinal cord lesions did not clearly meet the diagnostic criteria for NMOSD ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…As more understanding of it and more patients diagnosed, we speculated that it would become a new subtype of MS or a disease distinctive from MS. Since flotillins had been reported as a possible new marker of AD ( 11 , 12 ) and recently found in a patient of atypical dementia ( 8 ), besides classical symptoms and relapses, this patient’s cognition function requires further care during long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%